2008
DOI: 10.1016/j.actamat.2008.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Quench sensitivity of toughness in an Al alloy: Direct observation and analysis of failure initiation at the precipitate-free zone

Abstract: Analysis of toughness in 6156 Al-Mg-Si-Cu sheet has been performed using enhanced Kahn tear tests on samples quenched at different rates. Crack initiation energies were hardly affected by changing water quench temperature from 20°C to 60°C; however a significant reduction was evident on air cooling. Crack propagation energy was reduced for both 60°C water quenched and air cooled materials. Observation of failure initiation through synchrotron radiation computed tomography (SRCT), for the 60°C water quenched ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…Research into the characterization of PFZs is essential because they are believed to affect greatly the mechanical properties of these alloys. [1][2][3][4][5][6] Our work has also revealed that presence of PFZ adversely affects the fracture properties of the alloys by correlating mechanical properties to microstructual parameters. [7][8][9] It is known that small additions of various alloying elements (microalloying element) often change the morphology, spatial distribution and size of precipitates.…”
Section: Introductionmentioning
confidence: 97%
“…Research into the characterization of PFZs is essential because they are believed to affect greatly the mechanical properties of these alloys. [1][2][3][4][5][6] Our work has also revealed that presence of PFZ adversely affects the fracture properties of the alloys by correlating mechanical properties to microstructual parameters. [7][8][9] It is known that small additions of various alloying elements (microalloying element) often change the morphology, spatial distribution and size of precipitates.…”
Section: Introductionmentioning
confidence: 97%
“…In heat treatable Al-based alloys precipitation hardening is the dominant strengthening mechanism. For most commonly used alloys such as the Al-Mg-Si (6xxx) and the Al-Zn-Mg-(Cu) (7xxx) alloys, age hardening response can be seriously affected by the cooling rate from solution annealing (e. g. [1][2][3][4][5][6][7][8][9]; and also toughness can be reduced due to reduced cooling rate [10]. To achieve optimal mechanical properties, precipitation during quenching must be fully suppressed, and this is achieved only if the alloy is cooled with the upper critical cooling rate or faster (e. g. [4,8,7]).…”
Section: Introductionmentioning
confidence: 99%
“…La tendencia a la formación de precipitados no endurecidos es lo que se conoce como enfriamiento de sensibilización (Cavazos y Colás, 2003;Morgeneyer et al, 2008;Tiryakioğlu y Shuey, 2010). Examinados los efectos del enfriamiento sobre la variación que presenta el límite elástico de una aleación, esta variación es un indicador de la sensibilización del enfriamiento, conforme es mayor la velocidad de enfriamiento el límite elástico de la aleación va a ser menor.…”
Section: Enfriamiento De Sensibilizaciónunclassified